2019
DOI: 10.1515/hsz-2018-0204
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a protective role of the CX3CL1/CX3CR1 axis in a model of amyotrophic lateral sclerosis

Abstract: Aberrant microglial activation and neuroinflammation is a pathological hallmark of amyotrophic lateral sclerosis (ALS). Fractalkine (CX3CL1) is mostly expressed on neuronal cells. The fractalkine receptor (CX3CR1) is predominantly expressed on microglia. Many progressive neuroinflammatory disorders show disruption of the CX3CL1/CX3CR1 communication system. But the exact role of the CX3CL1/CX3CR1 in ALS pathology remains unknown. F1 nontransgenic/CX3CR1+/− females were bred with SOD1G93A/CX3CR1+/− males to prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…The use of primary hippocampal neuronal cultures enabled the observation of the neuroprotective effect of CX3CL1 against glutamate-produced toxicity, which was possible due to the presence of extracellular adenosine [ 110 , 111 ]. The role of the CX3CL1-CX3CR1 axis in neuronal survival and neurotrophic effects in the CNS were also indicated by other research groups [ 43 , 98 , 112 - 114 ].…”
Section: Chemokines and Clusters Of Differentiation In The Healthy Brmentioning
confidence: 65%
“…The use of primary hippocampal neuronal cultures enabled the observation of the neuroprotective effect of CX3CL1 against glutamate-produced toxicity, which was possible due to the presence of extracellular adenosine [ 110 , 111 ]. The role of the CX3CL1-CX3CR1 axis in neuronal survival and neurotrophic effects in the CNS were also indicated by other research groups [ 43 , 98 , 112 - 114 ].…”
Section: Chemokines and Clusters Of Differentiation In The Healthy Brmentioning
confidence: 65%
“…However, general information about the relevance of CX3CL1 and CX3CR1 in ALS is rather rare, except that disruption of MN-microglia communication as the result of CX3CR1 receptor deficiency in transgenic SOD1 G93A mice accelerates disease progression and exacerbates neuronal death [ 21 ]. This observation indicates that the protective role of CX3CR1 signaling has been proven [ 112 , 113 ]. In addition, CX3CR1 was postulated to be a potential gene that regulates the survival and progression of ALS [ 113 ].…”
Section: Cx3cl1/cx3cr1 Signaling In Neurodegenerative Diseasesmentioning
confidence: 77%
“…Recent findings have confirmed that intercellular communication between motor neurons and microglia plays an important role in the pathogenesis of ALS [ 108 , 111 , 112 ]. The neuron–glia interaction was disrupted even before the onset of ALS symptoms.…”
Section: Cx3cl1/cx3cr1 Signaling In Neurodegenerative Diseasesmentioning
confidence: 93%
“…Furthermore, it appears that the CX3CR1/CX3CL1 complex has also a neuroprotective effect while lacking either fractalkine (CX3CL1) or its receptor leads to neurodegeneration. Elevated microglia cell activation and neuronal loss have been also noticed in SOD1G93A/CX3CR1 −/− mice (Liu et al, 2019). One study showed that microglia can regulate the number of neural precursor cells in the developing brain.…”
Section: Microglial Cellsmentioning
confidence: 99%